Revising Basel 2 : the impact of the financial crisis and implications for developing countries (UN New YorkUS, 2010)
Discusses the rationale of the Basel 2 agreement and recent proposals for its revision in the light of developments which led to current financial crisis. Attempts to place these proposals in the context of the broader agenda for financial reform now being developed. Attempts to redress the balance with respect to emerging-market and other developing countries through consideration of issues related to introduction of Basel 2 in their jurisdictions as well as a review of approaches to its introduction that were actually adopted in selected countries.
Keywords: BANKING SYSTEMS